Analysis of poly(ADP-ribose) polymerase-1 by enzyme-initiated auto-PARylation-controlled aggregation of hemin-graphene nanocomposites. Issue 11 (17th April 2018) - Liu, Yong; Xu, Xiaolin; Yang, Haitang; Xu, Ensheng; Wu, Shuangshuang; Wei, Wei; Chen, Jin
Abstract : Poly(ADP-ribose) polymerase-1 (PARP-1) is a highly conserved nuclear enzyme, which binds tightly to damaged DNA and plays a key role in DNA repair, recombination, proliferation, and genomic stability. Abstract : Poly(ADP-ribose) polymerase-1 (PARP-1) is a highly conserved nuclear enzyme, which binds tightly to damaged DNA and plays a key role in DNA repair, recombination, proliferation, and genomic stability. However, due to the poor electrochemical and optical activity of PARP-1 and its product PAR, only a few studies on its activity detection method have been reported. Herein, we report a simple and sensitive colorimetric strategy to monitor PARP-1 activity based on enzyme-initiated auto-PARylation-controlled aggregation of hemin-graphene nanocomposites (H-GNs). PARP, activated by dsDNA, catalyzed its substrate nicotinamide adenine dinucleotide (NAD + ) to polymerize as a poly(ADP-ribose) polymer (PAR). PAR possesses several negative charges, and its charge density is twice that of a single-stranded DNA, which greatly impacts the dispersibility of H-GNs; due to their peroxidase-like catalytic activities, H-GNs can catalyze the chromogenic reaction of TMB and H2 O2 . As a result, in the presence of different PARP-1 activities, the supernatant of the corresponding solution contained different amounts of dispersed H-GNs and showed different colors after the chromogenic reaction that could be discerned easily by the absorbance or the color changes of the solution. The method was simple, sensitive, and reliable. The proposed method displays a linear range from 0.05 to 1 U with a detection limit of 0.03 U. In addition, this new method has been successfully applied to detect PARP-1 activity in human serum and different cancer cells and evaluate PARP-1 inhibitors.